A case of left ventricular pseudoaneurysm with long survival and congestive heart failure as first presentation. Case report and review of the literature - Varvarigos, Nikolaos; Koletsis, Efstratios; Zafiropoulos, Athanasios; Papaioannou, Harilaos; Migdalis, Ilias (Medical science monitor, 2005)
Left ventricular pseudoaneurysm is a rare and extremely fatal complication of acute myocardial infarction. It is defined as a rupture of the myocardium contained by epicardial adhesions or the epicardial wall. A 76-year-old woman was brought to our department suffering from acute pulmonary edema and left ventricular pseudoaneurysm. This condition was caused by an unrecognized high lateral myocardial infarction, which was diagnosed and treated conventionally. Four years after the diagnosis was made, the patient is in good physical condition. The presentation, imaging findings, and the prognosis of such cases are briefly discussed. We have especially focused on the imaging techniques currently used to confirm the diagnosis and on the fact that although the patient refused to have an operation (most appropriate for the diagnosis), she still lives in good physical condition (NYHA II). We report a case of post infarction pseudoaneurysm along with review of the literature on the subject. We discuss the role of computed tomography and magnetic resonance imaging to ascertain the diagnosis and the algorithm of therapeutic management. Based on current literature, we believe that surgical resection is the treatment of choice for patients in whom a pseudoaneurysm is detected within three months after myocardial infarction, for patients with other indications for cardiac surgery, and for symptomatic patients with ventricular tachycardia or recurrent embolism related to the pseudoaneurysm. Optimum medical therapy is the only alternative in those high-risk patients who refuse surgical operation.